The role of club activities in the development of students' musical abilities in general education schools - Khojageldiyeva Mahfuza Ergash qizi; Himmatova Nargiza Pardayevna; Panjiyeva Nilufar Kamol qizi (Zien Journals, 2022)
This article discusses the purpose of organizing music activities in general education institutions out of school and out of class, and their main tasks. These requirements for musical aesthetic education should be met in all parts of the education system in accordance with the content and essence of music-educational and music-educational goals and objectives, and in extracurricular activities students should be taught music-theoretical lessons. to strengthen their knowledge, to be able to apply it in practice, to be engaged independently in any type of musical art (according to their interests), to acquire special knowledge and skills of practical performance
Keywords: Music Clubs; Popular and Club Forms; VChA; Instrumental Ensemble